Hierarki Bangunan Permukiman Pegawai Pabrik Gula Kaliredjo Sumpiuh Banyumas (1909-1933): Hierarki bangunan permukiman pegawai pabrik gula Kaliredjo Sumpiuh Banyumas (1909-1933) - Nugroho, Arbani Aji; Assilmi, Ghilman (Berkala Arkeologi, 2023)
During the 19th century, industrialization in Indonesia resulted in the presence of many archaeological artefacts, including a sugar factory. Research on Kaliredjo sugar factory has never been conducted. This research aims to find out the social structure through the settlement pattern of Kaliredjo sugar factory. The method used in this research is an archaeological method in the form of data collection, processing, and interpretation. : Both primary and secondary data were gathered as they relevant to the issues addressed in this research. The data is processed by juxtaposing primary and secondary data. The processed data is analyzed using the lens of panopticon theory in order to address research inquiries. The findings of this study indicate the existence of a social framework and significance in the arrangement of residential buildings for employees of the Kaliredjo sugar Factory.